Meteopathies and arterial hypertension: causes, manifestations - E. G. Ivanova (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2021)
At present, the question of the influence of climatogeographic and meteorological factors on human health continues to be relevant and causes discussions among scientists and clinicians around the world. The aim is to study the manifestations and causes of pathological meteosensitivity in patients with arterial hypertension permanently residing in the Far North. For the period from June 2017 to March 2018, 138 patients with a confirmed diagnosis of arterial hypertension (AH) were included in the study based on generally accepted criteria (ESH/ESC, 2018), permanently living in the Far North. Men – 42 people (30.4 %), women – 96 people (69.56 %). The age of the study participants ranged from 18 to 65 years, averaging 45 ± 5.6 years. 32 people smoked (23.19 %). The condition for inclusion in the study was the presence of complaints about meteosensitivity, the manifestation of meteopathies against the background of changes in meteorological conditions, the short duration and relativity of these disorders in the same patient in the same weather conditions. The main meteorological elements that can be considered predictors of meteopathies have been determined, and the main manifestations  of  pathological  meteosensitivity  in  patients with  AH  permanently residing in the Far North have been identified. The presence of pathological meteosensitivity should probably be considered as an additional risk factor for the development of cardiovascular events. At present, details such as the manifestation of the metabolic syndrome in patients with hypertension, the degree of hypertension and the duration of the underlying disease, changes in biochemical parameters, and their associations with meteopathies require detail.